(untitled) (Journal of human and social sciences, 2023)
Foreign investments are among the most significant economic variables, playing a key role in generating productive capacities, which in turn increases the gross domestic product (GDP). They also finance economic development by transferring modern technology and diversifying income sources. The importance of this topic is highlighted from both economic and legal perspectives: economically, foreign investments contribute to the economic and social development of host countries by increasing foreign exchange revenues and introducing modern technology. Legally, legislators establish a special legal framework for investment through investment laws, as in Libya under Law No. (9) of 2010 on Encouraging Investment. Despite the issuance of this law, many questions arise regarding its effectiveness and contribution to forming strategies for reconstruction and policies to promote foreign investment.